Investigating junctional filopodia exchange - Tammi, Johanna (My University, 2024)
Metastasis is the leading cause of cancer-related deaths, driven by the ability of cancer cells to migrate from the primary tumour to other parts of the body. Filopodia, finger-like actin-rich protrusions, play a crucial role in migratory processes by facilitating interactions with the extracellular matrix (ECM) and neighbouring cells. While ECM-sensing filopodia have been extensively studied, the role of filopodia at cell-cell junctions, known as junctional filopodia, remains largely unknown. Previous unpublished results from our research group revealed that DCIS.com cells can internalise junctional filopodia. Three key proteins, Pacsin2, caveolin1 and dynamin2, were identified at filopodia invaginations on the receiving cell’s membrane, suggesting their involvement in the internalisation process. These proteins are important in endocytic processes and are also involved in trans-endocytosis, a direct intercellular exchange of materials, suggesting that a similar mechanism could drive filopodia internalisation. This study aimed to investigate whether junctional filopodia can be internalised in other cell types and whether Pacsin2, caveolin1 and dynamin2 are involved in this process. MYO10, a motor protein localised at the ends of filopodia, was used as a marker to visualise filopodia tips. U2OS cells expressing MYO10 were co-cultured with U2OS cells that had been transfected with fluorescent markers for Pacsin2, caveolin1, and dynamin2. High-resolution confocal microscopy was used to image both fixed and live cells. Additionally, to investigate Pacsin2’s role in more detail, an inducible silencing of Pacsin2 was made with shRNA. Results revealed that junctional filopodia can be internalised in U2OS cells. Live imaging showed the recruitment of Pacsin2 and caveolin1 to filopodia contact sites, suggesting their involvement in coating the emerging filopodia. The attempt to silence Pacsin2 was unsuccessful as no difference in protein levels was detected. Despite several challenges, our findings align with previous results, highlighting the need for further research into filopodia-mediated intercellular communication. Understanding filopodia dynamics could provide insights into novel pathways involved in cancer cell migration and metastasis, possibly leading to the identification of new therapeutic targets.
Keywords: junctional filopodia, Pacsin2, trans-endocytosis